FORECASTING SPOKE CAKE SALES AT ZAHRA SHOP WITH DOUBLE EXPONENTIAL SMOOTHING METHOD - Nurhaliza, Siti; Amin, Muhammad; Christy, Tika (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2023)
Abstract: Sales of sponge cakes at Zahra's shop have difficulty meeting customer demand when the demand for sponge cakes increases drastically at certain times. This is because the sales of sponge cakes at Zahra's shop are still calculated based on their own estimates, causing excess production to be made and even a shortage of sponge cake supplies. This problem has an impact on the supply control of sponge cake production which cannot be predicted properly by Zahra's shop. The purpose of this study is to build a forecasting system using the double exponential smoothing method to predict sales of sponge cake at Zahra's shop for the next period based on the data obtained. The research method used in this study is a quantitative method. The results in the calculation of sponge cake sales forecasting using the Double Exponential Smoothing method using alpha 0.5, the number of sponge cake sales for July 2023 on Banana Cake is 430 boxes, with a forecasting error rate of 2.75%, on Chiffon Mocca Sponge cake is 330 boxes, with a forecasting error rate of 2.75%. forecasting error of 4.50%, on Pandan Cake as many as 92 Boxes, with a forecasting error rate of 7.21%, on Ordinary Roll Cake as many as 77 Boxes, with a forecasting error rate of 4.78, So the error rate on Banana Cake, Bolu Chiffon Mocca, Pandan Cake, and Ordinary Roll Cake are in the very good category because they have an error value of less than 10%. Keywords : double exponential smoothing; forecasting; spoke cake Abstrak: Penjualan kue bolu pada toko zahra mengalami kesulitan untuk memenuhi permintaan pelanggan ketika permintaan kue bolu meningkat secara drastis diwaktu-waktu tertentu. Hal ini disebabkan karena penjualan kue bolu di toko zahra masih perhitungan berdasarkan perakiraan sendiri sehingga menyebabkan produksi yang dibuat sering kelebihan bahkan kekurangan persedian kue bolu. Masalah tersebut berdampak pada pengendalian persedian produksi kue bolu yang tidak dapat diprediksi dengan baik oleh toko zahra. .Tujuan penelitian ini adalah membangun sistem peramalan dengan metode double exponential smoothing untuk meramalkan penjualan bolu pada Toko Zahra untuk periode berikutnya berdasarkan data yang diperoleh. Metode penelitian yang digunakan dalam penelitian ini adalah metode kuantitatif. Hasil dalam perhitungan peramalan penjualan kue bolu dengan metode Double Exponential Smoothing menggunakan alpha 0.5 jumlah penjualan kue bolu untuk bulan Juli 2023 pada Bolu Pisang sebanyak 430 Kotak, dengan tingkat kesalahan peramalan sebesar 2,75%, Pada Bolu Chiffon Mocca sebanyak 330 Kotak, dengan tingkat kesalahan peramalan sebesar 4,50%, pada Bolu Pandan sebanyak 92 Kotak, dengan tingkat kesalahan peramalan sebesar 7,21%, pada Bolu Gulung Biasa sebanyak 77 Kotak, dengan tingkat kesalahan peramalan sebesar 4,78, Sehingga tingkat kesalahan pada Bolu Pisang, Bolu Chiffon Mocca,Bolu Pandan, dan Bolu Gulung biasa tergolong kategori sangat baik karena memiliki nilai kesalahan kurang dari 10%. Kata Kunci : peramalan; kue bolu; pemulusan eksponensial ganda